Effects of Mindfulness Based Stress Reduction Therapy on Subjective Bother and Neural Connectivity in Chronic Tinnitus. (24th February 2015) - Roland, Lauren T.; Lenze, Eric J.; Hardin, Frances Mei; Kallogjeri, Dorina; Nicklaus, Joyce; Wineland, Andre M.; Fendell, Ginny; Peelle, Jonathan E.; Piccirillo, Jay F.
Abstract : Objective: To evaluate the impact of a Mindfulness Based Stress Reduction (MBSR) program in patients with chronic bothersome tinnitus on the (1) severity of symptoms of tinnitus and (2) functional connectivity in neural attention networks. Study Design: Open‐label interventional pilot study. Setting: Outpatient academic medical center. Subjects: A total of 13 adult participants with a median age of 55 years, suffering from bothersome tinnitus. Methods: An 8‐week MBSR program was conducted by a trained MBSR instructor. The primary outcome measure was the difference in patient‐reported tinnitus symptoms using the Tinnitus Handicap Index (THI) and Tinnitus Functional Index (TFI) between pre‐intervention, post‐MBSR, and 4‐week post‐MBSR assessments. Secondary outcomes included change in measurements of depression, anxiety, mindfulness, and cognitive abilities. Functional connectivity magnetic resonance imaging (MRI) was performed at pre‐ and post‐MBSR intervention time points to serve as a neuroimaging biomarker of critical cortical networks. Results: Scores on the THI and TFI showed statistically significant and clinically meaningful improvement over the course of the study with a median ΔTHI of −16 and median ΔTFI of −14.8 between baseline and 4‐week follow‐up scores. Except for depression, there was no significant change in any of the secondary outcome measures. Analysis of the resting state functional connectivity MRI (rs‐fcMRI) data showed increased connectivity in the post‐MBSR group in attention networks but not the default network. Conclusion: Participation in an MBSR program is associated with decreased severity in tinnitus symptoms and depression and connectivity changes in neural attention networks. MBSR is a promising treatment option for chronic bothersome tinnitus that is both noninvasive and inexpensive.